Quality of thematic mapping based on multispectral images depending on the filed resolution - Bakó, Gábor (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
Highly detailed spatial data and thematical map databases are necessary for ecological, climatic and hidrological models, as well as for modern administrational and environmental decision making. The topography, land cover and habitat maps are made by interpreting different air and space images. These interpretations are not free of distortions. I tried to find the best resolution range for interpreting the different land cover elements. Determining optimal resolution range for the restriction of certain surface-cover categories, habitats and plant species has emerged as a demand during the research, by examining the extent of analysis distortion. I have restricted the basic qualitative characteristics and resolution necessary for the analytical methods of different thematic surface-covers. I found that the mapping of inhabited areas requires 1 m or higher field resolution of the basic raster image. Mapping of road and rail network, land farming areas, conservation perspective, extent of the damage assessment mapping requires 20 cm or higher resolution. 10 cm or higher geometric resolution basic image-maps good for thematic mapping of illegal waste deposals, areas of wildlife management, information for micro-climate modeling and the analysis of grassland habitats.Different land cover categories require basic images with different special resolution ranges. The quality of the basic photo-map determines the distortions of the interpretation.
Keywords: remote sensing; land cover mapping; nature conservation; land management